A contribution to the Slovenian spider fauna – V - Žan Kuralt; Neža Pajek Arambašič; Maja Ferle; Rok Kostanjšek (Natura Sloveniae)
The present study discusses and reports on 29 spider species new to Slovenian fauna, specifically: Larinioides patagiatus, Cyrtarachne ixoides, Pritha nana, Marinarozelotes adriaticus, Micaria micans, Scotophaeus blackwalli, Zelotes similis, Agyneta orites, Donacochara speciosa, Lasiargus hirsutus, Trichoncus sordidus, Walckenaeria vigilax, Alopecosa taeniata, Pardosa oreophila, Pardosa sordidata, Pardosa paludicola, Pardosa sphagnicola, Xerolycosa miniata, Mimetus laevigatus, Philodromus laricium, Philodromus vagulus, Attulus rupicola, Marpissa radiata, Micrommata ligurina, Euryopis quinqueguttata, Parasteatoda tabulata, Phoroncidia paradoxa, Rhomphaea rostrata, and Robertus mediterraneus.